Respiratory Function and Health-Related Quality of Life among Patients with Chronic Obstructive Pulmonary Disease (Community Based Medical Journal, 2025)
A cross-sectional study was conducted in the National Institute of Diseases of the Chest and Hospital (NIDCH), Dhaka, Bangladesh, from January to December of 2023, to assess the correlation between respiratory function and health-related quality of life (HRQoL) among COPD patients in Bangladesh. A total of 150 patients having chronic obstructive pulmonary disease (COPD) were selected for this study. Data were collected via face-to-face interviews, with spirometry measuring FVC, FEV1, and FEV1/FVC ratio, and QoL was assessed using the St. George's Respiratory Questionnaire-C. The socio-demographic profile of COPD patients showed that 62.7% were male, with the highest proportion (35.3%) aged between 60–69 years. Additionally, 32% reported a family history of COPD, 22% were current smokers, and 15.3% had a history of tobacco product use. In terms of BMI, 54.7% had a normal weight, 41.3% were overweight, and only 2% were either underweight or obese. Pulmonary function test results revealed mean values of FVC at 1.43±0.49, FEV1 at 0.85±0.32, and an FEV1/FVC ratio of 0.61±0.13. Regarding disease severity based on FEV1/FVC ratio, 30% of patients were classified as having moderately severe COPD, while only 1.3% had very severe COPD. SGRQ-C scores indicated a high symptom burden and significantly reduced quality of life among the patients. GLM regression analysis showed a significant association between greater COPD severity and lower health-related quality of life (p